Functional properties of electrolytic alloys of Cobalt with Molybdenum and Zirconium - Ved, M.; Koziar, M.; Sakhnenko, N. D.; Slavkova, M. (Institute for Single Crystals, 2016)
Functional electrolytic alloy coatings Co-Mo and Co-Mo-Zr were deposited on substrates steel 3 from polyligand citrate-pyrophosphate bath using pulsed current. It was shown that the alloying components content, their distribution on the surface, morphology and topography of the coatings are depended on the electrolysis energetic parameters. It was established that the functional properties of the binary and ternary electrolytic cobalt alloys (corrosion resistance, catalytic activity in hydrogen evolution and carbon II oxide oxidation) are predetermined by material composition, morphology and relief of the surface. Stability Co-Mn, and Co-Mo-Zr systems in aggressive media due to increased susceptibility to passivity when the molybdenum and zirconium are in the coating is a prerequisite of their use for corrosion protection. The high level of the catalytic properties of Co-Mn, and Co-Mo-Zr associated with different affinities for alloying metals to oxygen and hydrogen evolution mechanism verification allows to recommend them for platinum metals replacement in heterogeneous catalysis.

Функциональные электролитические покрытия сплавами Co-Mo и Co-Mo-Zr получены из полилигандного цитратно-пирофосфатного электролита в импульсном режиме на подложках из стали 3. Показано, что содержание легирующих компонентов, их распределение по поверхности, морфология и топография покрытий зависят от энергетических параметров электролиза. Установлено, что функциональные свойства бинарного и тернарного электролитических сплавов кобальта (коррозионная стойкость, каталитическая активность в реакциях выделения водорода и окисления оксида углерода II) предопределяются составом материала, морфологией и рельефом поверхности. Устойчивость систем Co-Mo и Co-Mo-Zr в агрессивных средах обусловлена повышением склонности к пассивации при включении молибдена и циркония в состав покрытий и является предпосылкой их использования для защиты от коррозии. Высокий уровень каталитических свойств Co-Mo и Co-Mo-Zr связан с различным сродством сплавообразующих металлов к кислороду и верификацией механизма выделения водорода и позволяет их рекомендовать для замены платинидов в гетерогенном катализе.
Функциональные свойства электролитических сплавов кобальта с молибденом и цирконием
Keywords: cobalt alloys; refractory metals; electrochemical synthesis; functional properties; pulsed electrolysis; citrate-diphosphate electrolyte; corrosion resistance; catalytic properties; сплавы кобальта; тугоплавкие металлы; электрохимический синтез; функциональные свойства; импульсный электролиз; цитратно-дифосфатный электролит; коррозионная стойкость; каталитическая активность